Theory and Practice of Algorithms in (Computer) Systems First International ICST Conference, TAPAS 2011, Rome, Italy, April 18-20, 2011. Proceedings - Marchetti-Spaccamela, Alberto; Segal, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the First International ICST Conference on Theory and Practice of Algorithms in (Computer) Systems, TAPAS 2011, held in Rome, Italy, in April 2011. The 25 papers presented, including three short papers by invited speakers, were carefully reviewed and selected from 45 submissions. The papers all feature original research in the design, implementation and evaluation of algorithms with special focus on algorithms for combinatorial optimization problems, and to real-world applications, engineering and experimental analysis of algorithms - thus fostering the cooperation among researchers in computer science, networking, discrete mathematics, mathematical programming and operations research.
Keywords: Computer science; Software engineering; Data structures (Computer science).; Computer software; Electronic data processing; Computer simulation; Computer Science; Algorithm Analysis and Problem Complexity; Mathematical Logic and Formal Languages; Software Engineering; Simulation and Modeling; Data Structures; Numeric Computing